Study of occurrence and correlation between allergic diseases and opisthorchiasis in the population of the Tomsk Region - L. M. Ogorodova; M. B. Freidin; A. E. Sazonov; O. S. Fedorova; I. E. Gerbek; N. A. Cherevko; A. A. Roudko; Ye. Yu. Bragina; T. V. Perevozchikova; Ye. A. Fait; N. Yu. Lebedeva (Бюллетень сибирской медицины, 2006)
The aim was to estimate the epidemiological and pathogenetic correlation between allergic diseases and opisthorchiasis in the population of Tomsk and the Tomsk Region. The program was a cross-sectional epidemiological snap study based on two samples: village inhabitants ( n = 201; mean age 12,1 ± 3,4) and Tomsk inhabitants ( n = 196; mean age 30,16 ± 12,86). The epidemiological, clinical, parasitological, allergological, immunological, and statistical methods were used in the study. It has been found that allergic diseases affected about 40.9% of village patients with opisthorchiasis and 26,1% people without parasites ( р < 0.05). For Tomsk inhabitants, this proportion was 54,5 and 52,6%.